A high performing piezoelectric and triboelectric nanogenerator based on a large deformation of the novel lantern-shaped structure. (February 2022) - Liu, Xu; Liu, Yizhi; Cheng, Tinghai; Gao, Yufei; Yang, Zhiqiang
Abstract: Energy shortage has been the most serious problem for generations. With the continuous consumption of fossil energy, there is an urgent need to find a renewable and sustainable energy source. However, the mechanical energy is ubiquitous and adequate in daily life. With the development of nanotechnology, nanogenerators can utilize and convert mechanical energy into electric energy, which provides an effective solution in modern society. Besides, the combination of functional materials, the coupling mechanism between piezoelectricity and triboelectricity as well as other methods can improve the output properties of nanogenerators to a large extent. Hence, in this paper, the raw materials of polyvinylidene fluoridetrifluoroethylene (PVDF-TrFE), barium titanate (BTO) together with polydimethylsiloxane (PDMS) are innovatively mixed to obtain both outstanding piezoelectricity and flexibility. In addition, from the structural perspective, the lantern-shaped nanogenerator (LSNG) with large deformation rate up to 86% and tri-piezoelectric and single-triboelectric coupling mechanisms is well fabricated. The output voltage, current and power density can go up to 171.2 V, 107.6 μA and 0.6 mW/cm 2, respectively. What's more, the pressure sensitivity of the LSNG approaches 46.37 ± 0.5 mV N −1 (R 2 = 0.997) in the pressure ranging from 5 N to 25 N. The whole LSNG can maintain a stable electrical output even after 10, 000 periodic operation cycles. Simulations were performed by using COMSOL and ANSYS in order to investigate the principle of the electricity generating and the relationship between strain and stress of the overall structure. Additionally, it can serve as a generator to light up several LED lights and collect mechanical energy from large deformations. Furthermore, it can serve as a sensor for detecting slight movements, mechanical position and realizing the patient positioning if integrated into the hospital floors. What's more, it can convert mechanical energy into electrical energy from vehicles, bicycles, pedestrians, etc. in a large scale once they are placed under the pavements. In the future, this LSNG will play an important role in converting the vibration energy into electric energy. In the future, this LSNG will play an important role in converting the vibration energy into electric energy. Graphical Abstract: ga1 Highlights: P(VDF-TrFE), BTO and PDMS were innovatively mixed and cured to conbine piezoelectricity with flexibility in one material matrix. The sidewall of the LSNG could meet the deformation up to 86% and the whole structure could keep a stable output after 10, 000 cycles. The output voltage, current, power density and sensitivity of LSNG were 171.2 V, 107.6 μA, 0.6 mW/cm 2 and 46.37 ± 0.5 mV/N (R 2 = 0.997) respectively. The LSNG were made into a matrix to serve as both the sensor and the functional keyboard, which showed the potential for sensing and energy converting.